Eficiência nutricional de fósforo, em estádios fenológico de aveia-branca - Dal’Maso, Vanessa (2020)
Mechanisms of plant adaptation to low availability of phosphorus (P) are related to the nutritional efficiency of some agricultural crops. However, it is not yet known how this varies in the phenological cycle and what are the important mechanisms for the nutritional efficiency of this nutrient in white oats. This study aimed to verify what are the mechanisms that influence the nutritional efficiency of phosphorus (NEP) and how it varies between some stages of the phenological cycle of this culture. The experiment was carried out in the field, in a humic dystrophic Red Latosol, in Passo Fundo, RS, in 2018. The experimental design was in randomized blocks. The white oat cultivars were URS Taura and UPFPS Farroupilha. The soil and plant samples used to evaluate the mechanisms and NEP were obtained from plots with low, medium, and high P availability. The mechanisms (mycorrhizal colonization, acid phosphatase, root morphology) and the types of nutritional efficiencies (rooting, acquisition, translocation, and use) were evaluated in tillering and anthesis. Nutritional efficiencies were also evaluated in physiological maturation. In tillering, the mechanism that is associated with acquisition efficiency was the root morphology (specific surface area, volume, and the number of root tips) beyond to acid phosphatase. In the anthesis, rooting efficiency is also associated with the same root morphological attributes (except the number of root tips). At this stage, although NEP is higher to tillering and physiological maturation. The colonization of native mycorrhizal fungi is not associated with any type of efficiencies, regardless of the assessed stage. The gene expression of P transporters is not conclusive, new primers and conditions will need to be tested.